STRATEGI PEMASARAN SYARIAH PADA PRODUK PEMBIAYAAN PERMATA MANFAAT DALAM MENINGKATKAN JUMLAH ANGGOTA DI MASA PANDEMI COVID 19 - Ziyadatur Rosyada; Saifuddin (ICO EDUSHA, 2022)
Thesis entitled "Sharia Marketing Strategies on Permata Benefit Financing Products in Increasing the Number of Members during the Covid-19 pandemic (case study at KSPPS BMT Permata Jawa Timur, Mojokerto)". ithlak rejects the framework of thinking that the financing product is in great demand because during the pandemic members are constrained in their economy so that the existence of these products can be a solution to the obstacles of members during the pandemic. Seeing the background of this problem, the question arises how the sharia marketing strategy on permata benefit financing products carried out by KSPPS BMT Permata Jawa Timur, Mojokerto in increasing the number of members during the Covid-19 pandemic and how to implement permata mannfaat financing products at KSPPS BMT Permata Jawa Timur, Mojokerto during the Covid-19 pandemic. The type of research used is field research that is descriptive qualitative, data sources used primary and secondary data, while data collection techniques through observation (observing activities at KSPPS BMT Permata), interviews (KSPPS BMT Permata staff and members) and documentation (supporting evidence obtained in the field) The result of this study is to increase the number of members KSPPS BMT Permata using a 4P strategy, namely: product strategy, price, place and promotion. The application of permata manfaat financing at KSPPS BMT Permata Jawa Timur is in accordance with sharia procedures and principles. Keywords: Marketing Strategy, Permata manfaat Financing, and BMT References Melati Julia Roikhani, (2021), Analisis Strategi Pemasaran Produk Pembiayaan Murabahah dan Mudharabah Pada Koperasi Usaha Bersama Tijarotun Thoyibah Pada Masa Pandemi Covid-19 Ditinjau Menurut Ekonomi Islam, UIN Suka, Riau. Marlina Nur Afifah, (2021), Analisis Strategi Pemasaran Pada Produk Pembiayaan Mikro 75Ib Pada Masa Pandemi Covid -19 (studi kasus Bank BRI syariah KK Tulungagung), skripsi IAIN Ponorogo. Triton TB, (2008), Marketting Strategi Meningkatkan Pangsa Pasar dan Daya Saing, (Yogyakarta: Tugu Publisher,) Kasmir, Etika Customer Service. Jakarta: PT. Raja Grafindo Persada, 2005 Muhammad, (2014), Manajemen Dana Bank Syariah, Jakarta: Rajawali Pers. Philip Kotler, (2005), Manajemen Pemasaran jilid Satu dan Dua. Jakarta: Prenhallindo. Rivai, H Veithzal, (2010), Islamic Banking, Jakarta : PT Bumi Aksara. Saifuddin Anwar, (2012), Metode Penelitian, Yogyakarta : Pustaka Pelajar Sugiyono, (2016), Metode Penelitian Kombinas, Bandung: Alfabeta Al-Qur’an digital